Traditions in the Discussions about the obrabotvane of Folklore in the Avtorski Pesni v Naroden Duh from Bulgaria - Lozanka Peycheva (Arts, 2020)
The avtorski pesni v naroden duh (authored songs in folk spirit) are a modern and multifaceted phenomenon, which has accumulated a rich history in Bulgarian musical culture. This research presents the essential characteristics of these songs and a two-part typology (1. authorized/avtorizirani folk songs; 2. newly composed songs ‘in folk spirit’), which is based on both models of authorship (according to Michel Foucault, authorial function is manifested in two basic forms of authorship—plagiarism and appropriation). This study provides an overview of some of the thematic debates that attempt to resolve the inevitable contradictions and tensions surrounding songwriting in folk spirit. The avtorski pesni v naroden duh have attracted the critical attention of Bulgarian musicians and society and have been the subject of lively discussions, criticisms, and controversy in numerous publications from the first decades of the 20th century to the present. This survey offers different perspectives, opinions and arguments focused on one of the main discussion topics related to the creation and functioning of the avtorski pesni v naroden duh: pro and contra the obrabotvane (transformation, polishing, processing, cultivation) of folklore. This problem has been at the heart of intellectual discussions since the 1930s and during the 1950s–1980s. The critical discussion of the question pro and contra the obrabotvane of folklore, with its whole inconsistency, complexity and impossibility to be reduced to unambiguous answers, leads to sharp confrontations between the holders of different opinions.